Professional development and interpersonal communication: Influence on vocational teachers teaching performance - Masduki Ahmad; Heni Rochimah (Jurnal Pendidikan Vokasi, 2022)
This research was conducted to see the impact of professional development and interpersonal communication on the teaching performance of vocational teachers in  West Cikarang, West Java Province, Indonesia. The research method used is the survey method and data examination, namely multiple linear regression. The populace in this research was 119, with the Slovin formula with a 5% of significance level, then the research sample obtained was 92 vocational teachers. Data collection techniques using questionnaires and hypothesis testing using t-test and F-test. The outcome of this calculation shows that professional development and interpersonal communication on teacher teaching performance have simultaneous effects as indicated by the Fcount 34.453 > Ftable 3.10 and the significance value 0.000 > 0.05. The large effect of professional development and interpersonal communication on teaching performance is shown throughout the coefficient determination of 0.443 or 44.3%, with the influence of professional development variables of 13.9% while interpersonal communication variables of 30.2%.